Effect of botulinum neurotoxin of Mendoza clostridium botulinum atrain on tubulin in breast carcinoma cells (MCF 7) - Chapana, Agostina Lucía (2020)
Botulinum neurotoxin serotype A (BoNT A), produced by Clostridium botulinum, causes botulism and is used to treat multiple diseases. Its potential action in cancer therapy is currently being evaluated. In precedent studies, we have shown that BoNT A from native soil strains (Su), they have different characteristics to that of the prototype A Hall strain such as; greater specific toxic activity (AE) and differences in molecular structure and enzymatic activity against SNARE proteins. In this work, we study the action of an autochthonous BoNT A compared to the A Hall on tubulin in the MCF-7 cell line of breast carcinoma. The autochthonous BoNTs of the strain Su 1935 (Tupungato) and A Hall were used in their native form, purified by saline precipitation. The values of AE (LD50/mg protein) and electrophoretic characteristics under non-denaturing conditions were determined. MCF7 cells were cultured on coverslips and incubated with 250 and 500 LD50 of the BoNTs for 10, 25, 45, and 90 min. Later, the cells were fixed and processed for immunodetection. As primary antibodies were used anti-tubulin or anti-Golgina 97 and as secondary anti-mouse-Alexa 488. The preparations visualized by fluorescence microscopy. At 90 min incubation with 250 LD50, it was observed that ~90% of the cells were taken off and deformed by the action of the BoNT A 1935 and ~40% for the BoNT A Hall, while with 500 LD50 both toxins were deleterious to the cells. When the cells were incubated with the toxins for 25 min, a disruption of microtubules with both toxins was observed, the effect being greater with the BoNT A1935. This effect was accompanied by a redistribution of the Golgi apparatus. Western blotting showed the shape of new tubulin bands, possibly due to protein degradation. This effect was also greater in the BoNT 1935. These results show a cytotoxic action of BoNT A with disorganization of cell microtubules, being observed with greater intensity in the cells treated with the autochthonous BoNT A. The degradation of tubulin and its intracellular reorganization would be part of the deleterious action of this toxin on tumor cells, opening new perspectives for therapy against solid tumors.